Iraq experience in handling the COVID-19 pandemic: implications of public health challenges and lessons learned for future epidemic preparedness planning. (14th October 2021) - Lami, Faris; Rashak, Hiba Abdulrahman; Khaleel, Hanan Abdulghafoor; Mahdi, Sinan Ghazi; Adnan, Firas; Khader, Yousef S; Alhilfi, Riyadh A; Lehlewa, Asaad
Abstract: Background: Iraq has been exceptionally challenged by the COVID-19 pandemic due to the already exhausted healthcare system. Objectives: To describe the epidemiological situation of COVID-19 in Iraq, the government's response to the pandemic, and provide recommendations for further action. Methods: A desk review of secondary data using the available reports on the epidemiological situation in Iraq as well as official governmental sources was conducted. Results: The major surge in the number of COVID-19 cases occurred in the first week of June and continued to increase dramatically until mid-October when a significant decrease happened. With a few exceptions, the reproductive number R has been consistently above 1. Patients aged 30–39 years (25.6%) were the most affected, while those aged 60–69 years (26.7%) had the highest deaths rates. Iraq tried to contain the pandemic through several regulations: border control, enforcing curfew, mask-wearing, and social distancing, COVID-19 isolation centers, expanding lab capacity, contact tracing, as well as several supportive economic measures. However, the extent of implementing these regulations is questionable. Conclusion: Additional administrative and scientific measures with special emphasis on handling mass gathering, coordination with media and better training of healthcare workers particularly on infection prevention and control.